Quality, nursing service quality, accreditation standards, standards of nursing practice - سعيد سناء عبد الرحيم; كاظم علي حسن (Journal of Economics and Administrative Sciences, 2016)
Abstract health organizations are trying to introduce services of high quality and efficiency which requires applying some standards of nursing career to improve nursing service quality in the hospital, which provides an essential data base key to diagnosis the negative and positive part in nursing services to guarantee the quality of services presented . The aim of this study is to evaluated the quality of nursing service through stating the indicators of nursing career standards by comparing the reality of the a hospital with what should standards . In addition , adapting nursing career standards with what is suitable for hospital environment. The study has acquired its importance because it handles the reality of daily work of introducing nursing services in the hospital in the light of existing standards, and it provides a data base useful for hospital daily work to facilitate the process of evaluating the services continuously. The statistical methods used in this study are (the percentage, mean, standard deviation ,weighted average.. etc.). through them, the reality of nursing service in the hospital is diagnosed reaching to number of conclusions, the most important of them are , achieving the service quality that all organizations are trying to; today, The study has reached into a number of recommendations, the most important of them are, to cooperate coordinate with the top authorities as Ministry of Health, the necessity of dependence quality standards for nursing service to match with nursing developments ; and to develop the organizational structure of nursing by adding a quality management department ; forming of a committee for accreditation and quality to enhance nursing field, and evaluating how nursing correspond with the world standard